(untitled) (Czech Journal of International Relations, 2019)
This edited volume explores the different ways in which members of the European Union have interacted with Kosovo since it declared independence in 2008. While there is a tendency to think of EU states in terms of two distinct groups – those that have recognised Kosovo and those that have not – the picture is more complex. Taking into account also the quality and scope of their engagement with Kosovo, there are four broad categories of member states that can be distinguished: the strong and weak recognisers and the soft and hard non-recognisers. In addition to casting valuable light on the relations between various EU members and Kosovo, this book also makes an important contribution to the way in which the concepts of recognition and engagement, and their relationship to each other, are understood in academic circles and by policy makers.